The Evaluation of Trochlear Osseous Morphology: An Epidemiologic Study. Issue 7 (31st July 2020) - Yalçin, Sercan; Onor, Gabriel; Kaar, Scott; Pace, lee; Ferrua, Paolo; Farrow, Lutul
Objectives: The purpose of this study is to investigate the prevalence of the trochlear dysplasia in our study population. Methods: We obtained 692 skeletally mature femoral specimens from the [Blinded Institution], [Blinded Collection]. Five observers were asked to evaluate each specimen for trochlear dysplasia on a scale between 0 and 3 (0 – normal/no dysplasia; 1 – mild dysplasia; 2 – moderate dysplasia; 3 – severe dysplasia). Each observer made initial evaluations for interobserver reliability. Each observer then re-evaluated each specimen one month later to determine intraobserver reliability. We evaluated inter and intraobserver reliability utilizing intraclass correlation coefficient (ICC). All statistics were performed with SPSS v.25 (IBM, USA). Results: The interobserver ICC of first and second evaluation of all observers were found to be 0.906 [0.894-0, 916] and 0.904 [0.892-0.915], respectively. The intraobserver ICC of observers were as follows: Reviewer1: 0.799 [0.771-0.825]; Reviewer2: 0.686 [0.645-0.724]; Reviewer3: 0.808 [0.781-0.832]; Reviewer4: 0.787 [0.757-0.814]; Reviewer5: 0.778 [0.747-0.806]. These results show intra and interobserver correlation was good to excellent. The percentages of normal trochlea, mild dysplasia, moderate dysplasia and severe dysplasia for first evaluation, by reviewer, are as follows: Reviewer 1: 82.7%, 12.1%, 4.0%, 1.2%; Reviewer 2: 37.3%, 26.2%, 27.5%, 9.1%; Reviewer 3: 57.9%, 28.0%, 12.1%, 1.9%; Reviewer 4: 64.2%, 25.6%, 7.7%, 2.6%; Reviewer 5: 65.6%, 14.9%, 12.3%, 7.2%. The percentages of normal trochlea, mild dysplasia, moderate dysplasia and severe dysplasia for second evaluation, by reviewer, are as follows: Reviewer 1: 78.8%, 16.6%, 3.6%, 1.0%; Reviewer 2: 40.3%, 26.4%, 23.3%, 10.0%; Reviewer 3: 42.2%, 35.1%, 18.8%, 3.9%; Reviewer 4: 57.4%, 31.9%, 8.2%, 2.5%; Reviewer 5: 73.7%, 8.2%, 9.7%, 8.4%. In total, the percentages of normal trochlea, mild dysplasia, moderate dysplasia and severe dysplasia were 60.00%, 22.51%, 12.72%, 4.77%; respectively. Conclusions: This study shows that although there was no absolute criteria to grade trochlear dysplasia, observers had similar opinions on the degree of dysplasia. Also, our cohort shows that moderate to severe dysplasia is not uncommon as it is present in around 17% of knees in our cohort. This is the first epidemiologic study evaluating the prevalence of trochlear dysplasia in the normal population.